2021
DOI: 10.3390/min11020134
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a Chemical Washing Method for Treating Soil Enriched with Fluorine Derived from Mica

Abstract: High levels of fluorine in soil may pose health risks and require remediation. In this study, the feasibility of using a practical chemical washing method for the removal of fluorine from an enriched soil was evaluated. The chemical washing procedures were optimized through experimental analyses of various washing solutions and washing conditions (i.e., washing solution concentration, solid–liquid ratio, agitation speed, and reaction time). Additionally, the effects of techniques for improving the washing effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The target site of this study has been reported to exceed the Korean worrisome level of soil contamination (level 2 area: 400 mg/kg), owing to the accumulation of F in the soil through the weathering of mica, such as biotite, lepidolite, muscovite, and phlogopite [19]. The F-enriched soil of this site had a residual fraction of more than 99% [19].…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…The target site of this study has been reported to exceed the Korean worrisome level of soil contamination (level 2 area: 400 mg/kg), owing to the accumulation of F in the soil through the weathering of mica, such as biotite, lepidolite, muscovite, and phlogopite [19]. The F-enriched soil of this site had a residual fraction of more than 99% [19].…”
Section: Introductionmentioning
confidence: 86%
“…Since it is a site where underground development is planned in the future, it is necessary to confirm the contamination characteristics and remediation efficiency of the soil in a relatively deep depth. The study site soil contains accumulated F derived from mica minerals [19]. After releasing the particles that had aggregated through wet disintegration, the gravel was separated using a 2-mm sieve (10 mesh).…”
Section: Sample Preparation and Characterizationmentioning
confidence: 99%
See 3 more Smart Citations